Assistance of differentiated learning workshop for sekolah penggerak in independent curricullum - Pika Merliza (Balai Diklat Keagamaan Ambon, 2023)
Assistance is carried out with the aim that participants from sekolah penggerak program batch 2 can fully understand the concept of learning that is embedded in students, understand the school ecosystem that becomes students to train examples of learning that strengthens students so that they are committed to being willing to apply learning and ecosystems that contain learners. Mentoring activities are carried out using the service learning method, with the MERRDEK stage, the initial stage begins with opening up, starting from self, exploratory concepts, collaboration spaces, contextual demonstrations, elaboration of understanding to real action plans. The results of the mentoring activities include, activity participants demonstrate an understanding of the learning concepts assigned to students, facilitating differentiated learning based on the characteristics of the assessment results and student readiness both through document learning tools and through simulations of teaching practice.